Development of retrofitting solutions: Remedial wall ties for masonry enclosure brick walls - Rebelo, Filipe (2021)
The external envelope walls of a significant percentage of the residential building stock in Southern European countries is commonly constituted by infill masonry walls. However, thousands of square meters of this masonry wall typology presents severe issues of cracking and instability, related to the incorrect and deficient support conditions of the outer brick panel of the double-leaf wall solution. In this work, an experimental campaign divided in two phases has been performed to evaluate the effectiveness of two different remedial wall ties retrofitting techniques (Solution A and Solution B) used for double leaf horizontally hollowed clay brick masonry façades. The first phase of the experimental campaign was performed on 120 isolated specimens of horizontally hollowed clay bricks, resorting to post- and pre-NP EN 771-1 brick exemplars (that is, new and pre-existent aged bricks, respectively), as well as on 4 square wallettes, with a side length of 1.20 m, considered as representative of a real scale scenario, for evaluating the two remedial wall ties retrofitting techniques. The second phase of the experimental campaign was performed to fully characterize the different failure types as well as the slipping phenomena observed in the first phase of the experimental campaign, focusing solely on the retrofitting technique Solution B and comprises 24 tests performed on isolated specimens, resourcing to new and pre-existent aged bricks as well. The results obtained by the use of these techniques revealed an average anchorage strength value ranging from 0.25 to 2.5 kN for each tested tie-bar. Solution B reveals an increase of double of the anchorage strength value in comparison to Solution A. In this sense, the global results revealed a suitable applicability of both retrofit studied solutions.